Optimization of high-intensity resistance exercise protocols for improving bone mineral density in the elderly without chronic diseases: a systematic review and network meta-analysis - Cheng, Yang; Yi, Yue; Bo, Shumin; Mao, Jun; Ma, Jing (Frontiers in Physiology, 2025)
ObjectiveThis study aims to explore the effects of high-intensity resistance exercise (HIRE) protocols on improving bone mineral density (BMD) in the elderly without chronic diseases by using a forest plot and network meta-analysis.MethodsA systematic search was performed across seven databases including PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, Wan Fang and VIP, to investigate the effects of HIRE on BMD in the elderly by December 9, 2024. The search strategy incorporated Boolean operators (AND, OR, NOT) to refine the selection of relevant studies. The methodological quality was assessed by using Risk of Bias tool 2 and Tool for the Assessment of Study Quality and Reporting in Exercise, and data analysis was performed using Stata 17.ResultsA total of 13 RCTs involving 616 participants were included. Among the various HIRE protocols, two demonstrated positive effects on lumbar spine and whole-body BMD, while four were positive in improving femoral neck BMD compared to the control group. The network meta-analysis revealed that 3M(9–10) was more effective than 2M(6–8), 3M(6–8) and 1M(6–8) in enhancing lumbar spine BMD. However, no significant differences were observed among the HIRE protocols for femoral neck and whole body BMD. According to the SUCRA rankings, 3M(9–10) was the most effective protocol for improving lumbar spine (94.7%) and femoral neck BMD (82.3%), while 2M(9–10) ranked highest for whole body BMD improvement (61.6%).ConclusionHIRE protocol is critical to ensure BMD improvement for elderly without chronic diseases, and not all HIRE protocols yield positive effects on BMD. Compared to other sites, lumbar spine BMD appears to be more responsive to HIRE. A 2–3 times, multiple-set regimen may be more beneficial for improving lumbar spine, whole-body, and femoral neck BMD in the elderly, and performing 9–10 repetitions per set is particularly important for improving BMD in older adults.Systematic review registration numberhttps://www.crd.york.ac.uk/PROSPERO/, identifier registration number. CRD42024543517.